Matrix on Virtual Teaching: A Competency-Based Model for Faculty Development - Mary Rose Grant; V.J. Dickson (Adult Education Research Conference, 2008)
This model integrates the outcomes of a prior study of best practices for effective teaching in the online environment. This competency-based model expands emergent themes within the best practices and employs a generative approach to developing faculty as adult learners and builds on their existing knowledge encouraging further inquiry.
Keywords: faculty development; distance education; adult learning theory; competency-based model; part-time faculty